Revealing Masculinity in BTS’s Music: Between Self Identity and Market Desire - Frizki Yulianti Nurnisya; Sofia Hasna (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2023)
Previous studies assessed that the Korean Wave, including the music group Bangtan Sonyeondan (BTS), had campaigned for a different side of masculinity. BTS, through their music, seems to carry the concept of a "female-friendly model of masculinity". This feminine masculine identity is attached to BTS members and creates a typical stereotype of Asian men in the United States. This study aims to determine the representation of masculinity displayed by the boy group BTS in their video clips from 2013 to 2021 and observe at least 33 video clips. The researcher observed the symbol representation in the video clip with a Critical Discourse Analysis from Norman Fairclough and then conducted a thematic analysis by Braun and Clarke. The results showed a change in the representation of masculinity throughout their careers. This change in representation is also a form of compromise and negotiation between BTS as artists and the music industry's demands at an international level